Marketing of Political Communication Created by National Mandate Party (PAN) in General Election 2005-2015, North Sumatra, Indonesia - Anang Anas Azhar (Budapest International Research and Critics University, 2018)
PAN establishes itself as an open, independent party, upholding religious morality, humanity and pluralism, aimed at enlightening the nation. PAN is a party born from the womb of the reform movement founded by the figures of reforms across ethnic, racial, religious and class. It is rooted in religious morals, humanity and pluralism. DPW PAN in North Sumatra utilizes various channels of communication, not just to build the image but broader than that, it is to market political communication, strengthen the emotional connection with constituents. The process of marketing is carried out continuously, not only in the run up to election or election events, such as general election of regional but also after the election is done.